Corner in the Sewing room C.P.S. San Luis Obispo, Cal - Frank Aston::::::photographer:::
Two women students seated at sewing machines; one (L) is using machine; other (R) is trimming thread; Singer logo is visible on center machine; at least one machine is connected to electrical chord.